Investiments in distressed assets in Brazil - Sustek, Matthias (2018)
Investment in distressed assets, while relatively mature in developed markets, has become more and more common in Brazil in a context of a lingering economic downturn, offering interesting but risky opportunities to domestic and foreign investors. The distressed securities in Brazil are particularly challenging to invest in, a lot of them being deemed worthless in the first place by bigger institutions. Therefore, this research wants to understand how it is possible to create value out of these securities in such a delicate context. However, such subject remains widely unexplored in emerging markets with the literature emphasizing such shortcomings. To cope with the lack of information, this study intends to directly inquire with seasoned professionals in the field of distressed securities in order to obtain the knowledge where it can be found. As a result, the study shows that the market of distressed assets is very singular in Brazil and market participants needed to adapt to the context. Value creation relies on a whole local ecosystem of corporate lawyers, restructuration/turnaround consultants and asset managers. They are able to create value with very special sets of competences, mainly their management of information, their legal expertise and strategic management.